ВЕРОЯТНОСТЬ «СРЕЗА» ИМПУЛЬСОВ ТОКА В КОНТУРЕ ЕМКОСТНОГО НАКОПИТЕЛЯ ЭНЕРГИИ С ВАКУУМНЫМ РАЗРЯДНИКОМ - Лютенко , Л.А.; Михайлов , В.М. (Інститут електродинаміки НАН України, Київ, 2012)
The statistic of arise of interruption current pulses in discharge circuit of magnetic-pulse plant with controlled vacuum discharger to charge voltage and capacity of capacitor bank ratio is obtained. The duration and amplitude of first half-wave of current pulse are changed ranges from 130 μs to 200 μs and from 18 kA to 67 kA. The current rate in going from first half-wave to second half-wave of current pulse is estimated. The intervals of the more probability of arise of interruption current pulses are determined. References 4, figures 3.